RESEARCH ON PHYSIOLOGICAL AND ANATOMICAL CHARACTERISTICS OF AFZELIA XYLOCARPA (KURZ) CRAIB AT THE NURSERY - Douangmala, Sounthone; Van Viet, Nguyen; Quang Trung, Do; Viet Ha, Tran (Journal of Forestry Science and Technology, 2019)
Afzelia xylocarpa (Kurz) Craib is a high economic value plantation with many significant characteristics such as durable and beautifully patterned wood well tolerated in environmentally stressed conditions. This paper provides preliminary results about anatomical and physiological characteristics of Afzelia xylocarpa planting at the nursery. The result shows that Afzelia xylocarpa has some interesting phenotypes such as ratio of palisade and spongy parenchyma, 0.71, no multi-epidermis or covered hair. In addition, the result presents the stomata which lies horizontally with the epidermal layer where the average number is 602/mm2 and the total content of chlorophyll in fresh leaves is 10.42 mg/g with the ratio of a/b chlorophylls 1.49. The physiological data illustrates the evapotranspiration intensity, 0.63 g/dm2/h, and the water absorption figure, 14.09 atm. Moreover, the result also indicates that different temperatures (45, 50 and 600C) had a different effect on leaf tissues that was demonstrated by damaged/fresh ratios, 14.5%, 72% and 100%, respectively. All the above evidence suggests that Afzelia xylocarpa may need a medium intensity of light, would lose water easily and shows weak ability to water adsorption. These might play important roles in planting Afzelia xylocarpa in the future.